Do Indian physicians heal themselves? An online cross-sectional survey of health access behaviour of doctors at a tertiary-care hospital in South India - Poorvi Tatia; Syed Ilyas Shehnaz (Elsevier, 2022)
Background: The conflict of a doctor presenting as a patient is very much perceived in healthcare profession. Often overlooked, the well-being of physicians is an essential prerequisite to the health services they provide to their patients. Hence we aimed to assess the healthcare access behaviours of doctors of Saveetha Medical College and Hospital, Chennai, India and analyse barriers experienced by them in accessing healthcare. Methods: After obtaining Institutional ethical clearance, all consenting doctors were administered a structured, validated questionnaire via WhatsApp and SMS. Means and proportions were calculated and Pearson's Chi-square test of significance was used to identify association among variables. Results: Poor health-access behaviour was observed among majority of the 111 doctors who participated in the study. Familial involvement in healthcare was reported with 65% allowing their family to intervene in their health matters and 78.5% seeking consultation from their medically-qualified relatives. Younger (p = 0.026) and less experienced doctors (p = 0.18) were significantly more satisfied with self-treatment with no need felt for a primary care physician. Majority (75.7%) of doctors were inclined to informally consult for their personal medical conditions before seeking formal care. The respondents who weren't taking prescription medicines had significantly (p = 0.01) positive attitudes towards healthcare access. The major barriers in healthcare access were preference for informal consultations; worry about imposition on other busy doctors, pressure to stay healthy and long duty hours. Conclusion: Indian doctors identified significant barriers in healthcare access. Strategies directed at enhancing doctors' healthcare access should focus on tackling their professional culture of self-reliance.